Comparative Efficacy of Amoxicillin Versus Azithromycin in the Treatment of Pediatric Community-Acquired Pneumonia - Khurram Nawaz, Husnul Hayat, Rizwan Mahmood, Imran Yasin, Sanwal Sardar Nawaz, Muhammad Usman Rafique, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Community-acquired pneumonia is one of the leading causes of morbidity and mortality among children worldwide. Objective: To compare the clinical efficacy, safety, and treatment outcomes of amoxicillin versus azithromycin in the management of pediatric community-acquired pneumonia. Methodology: This comparative observational study was conducted at Department of Pediatric Medicine, Shahida Islam Medical & Dental College, Lodhran from 1st January 2023 to 30th June 2023 and included 355 children aged 6 months to 12 years diagnosed with community-acquired pneumonia. Patients were randomly divided into two equal groups: Group A received oral amoxicillin (50 mg/kg/day in three divided doses for seven days), while Group B received oral azithromycin (10 mg/kg on day one followed by 5 mg/kg once daily for four days). Clinical improvement was assessed on days 3 and 7 through resolution of fever, cough and tachypnea. Results: The mean age of participants was 5.8±2.9 years, with a near-equal gender distribution. Clinical cure was achieved in 91.6% of the amoxicillin group and 87.6% of the azithromycin group (p=0.21). Fever resolution within 72 hours occurred in 83.1% and 78.5% of patients, respectively. Both groups demonstrated significant reductions in white blood cell count and C-reactive protein levels by day 7, with no statistically significant difference between them. Adverse effects were mild and comparable, with diarrhea and nausea being the most frequent. The mean duration of hospital stay was slightly shorter in the amoxicillin group (3.8±1.2 days) than in the azithromycin group (4.0±1.3 days), though not statistically significant (p = 0.17). Conclusion: Both amoxicillin and azithromycin were effective and well-tolerated in the treatment of pediatric community-acquired pneumonia. Amoxicillin demonstrated a marginally faster clinical response and shorter hospital stay, reaffirming its role as the preferred first-line antibiotic for most pediatric CAP cases. Keywords: Amoxicillin, Azithromycin, Community-acquired pneumonia, Pediatrics, Antibiotic efficacy, Respiratory infection